A pulsed single-frequency Nd:GGG/BaWO4 Raman laser. (28th February 2018) - Liu, Zhaojun; Men, Shaojie; Cong, Zhenhua; Qin, Zengguang; Zhang, Xingyu; Zhang, Huaijin
Abstract: A single-frequency pulsed laser at 1178.3 nm was demonstrated in a crystalline Raman laser. A crystal combination of Nd:GGG and BaWO4 was selected to realize Raman conversion from a 1062.5 nm fundamental wave to a 1178.3 nm Stokes wave. An entangled cavity was specially designed to form an intracavity Raman configuration. Single-longitudinal-mode operation was realized by introducing two Fabry–Perot etalons into the Raman laser cavity. This laser operated at a pulse repetition rate of 50 Hz with 2 ms long envelopes containing micro pulses at a 30 kHz repetition rate. The highest output power was 41 mW with the micro pulse duration of 15 ns. The linewidth was measured to be less than 130 MHz.